1998
DOI: 10.1002/(sici)1097-4644(19981215)71:4<479::aid-jcb3>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages and antioxidant status in the NOD mouse pancreas

Abstract: This study showed that citiolone (CIT), a free radical scavenger, significantly increased superoxide dismutase (P < 0.001 vs. untreated NOD, NMMA-treated, and silica-treated animals), catalase (P < 0.01 vs. untreated NOD), and glutathione peroxidase (P < 0.001 vs. untreated NOD and C57BL6/J) values. Silica treatment was capable of counteracting the plasma antioxidant capacity (TRAP) decrease observed in untreated NOD mice, although it did not block the blood glucose rise and insulitis progression in type 1 dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…The reduced levels of antioxidant enzymes in the pancreas seen here are consistent with previously reports examining NOD mice (22), and diabetic rats induced by streptozotocin (23). …”
Section: Discussionsupporting
confidence: 92%
“…The reduced levels of antioxidant enzymes in the pancreas seen here are consistent with previously reports examining NOD mice (22), and diabetic rats induced by streptozotocin (23). …”
Section: Discussionsupporting
confidence: 92%
“…The reason for this species difference is not clear, but it suggests a difference in the role of LRP5 in the pathogenesis of Type I diabetes in the two species. The fact that ␤-cells are normally antigen-presenting, whereas ␣-cells are not, supports this contention (Papaccio et al 1998). To date, the region of the mouse genome that contains the mouse LRP5 orthologue has not been linked to NOD diabetes.…”
Section: Discussionmentioning
confidence: 94%
“…Macrophages mediate islet damage through ROS, NO, and cytokine production. Therefore, suppression of macrophages or inhibition of their activity was shown to slow insulitis progression in NOD mice (29) or prevent MLDS-induced diabetes (22,30,31). We recently reported that increased mitochondrial ROS production in Ucp2-KO macrophages allows quicker and stronger p38 and ERK signaling, leading to increased cell activity (8).…”
Section: Discussionmentioning
confidence: 99%